2018
DOI: 10.3389/fgene.2018.00217
|View full text |Cite
|
Sign up to set email alerts
|

Functional Partitioning of Genomic Variance and Genome-Wide Association Study for Carcass Traits in Korean Hanwoo Cattle Using Imputed Sequence Level SNP Data

Abstract: Quantitative traits are usually controlled by numerous genomic variants with small individual effects, and variances associated with those traits are explained in a continuous manner. However, the relative contributions of genomic regions to observed genetic variations have not been well explored using sequence level single nucleotide polymorphism (SNP) information. Here, imputed sequence level SNP data (11,278,153 SNPs) of 2109 Hanwoo steers (Korean native cattle) were partitioned according to functional anno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
45
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 42 publications
(51 citation statements)
references
References 63 publications
5
45
1
Order By: Relevance
“…The significantly associated SNPs for The proportions of genomic variance attributed to the regulatory SNPs were found to be 0.29, 0.25, 0.29, and 0.38 for BFT, CWT, EMA, and MS, respectively (Table 1). This is between 44% and 77% of the heritability estimated in a previous study using 11.2 million SNPs from across the genome of Hanwoo [1], suggesting that the regulatory SNPs might have a large effect on the traits evaluated in this study. This is consistent with previous reports that had reported that the missense variants (non-synonymous variants) are able to capture a large proportion of the genetic variance in beef and dairy cattle [12,57].…”
Section: Genome-wide Association Studymentioning
confidence: 54%
See 4 more Smart Citations
“…The significantly associated SNPs for The proportions of genomic variance attributed to the regulatory SNPs were found to be 0.29, 0.25, 0.29, and 0.38 for BFT, CWT, EMA, and MS, respectively (Table 1). This is between 44% and 77% of the heritability estimated in a previous study using 11.2 million SNPs from across the genome of Hanwoo [1], suggesting that the regulatory SNPs might have a large effect on the traits evaluated in this study. This is consistent with previous reports that had reported that the missense variants (non-synonymous variants) are able to capture a large proportion of the genetic variance in beef and dairy cattle [12,57].…”
Section: Genome-wide Association Studymentioning
confidence: 54%
“…The genotypes were then phased using Eagle v.2.3.2 [30] and then imputed, one chromosome at a time, using Minimac3 [31], to a high-density level, using a reference population consisting of 480 animals genotyped with Bovine HD BeadChip (777,962 SNPs). They were then imputed to the sequence level one chromosome at a time, using whole genome sequence data of a reference population of 311 progeny tested Hanwoo bulls [1], resulting in a total of 27,980,473 SNPs; the imputation pipeline followed for imputing from 770K to the sequence level was the same as the one used for 50K to HD imputation. Following a previous study [32], only SNPs with Minimac3 imputation quality statistic (R 2 ) higher than 0.4 were retained for further analysis, resulting in a total of 12,980,473 SNPs.…”
Section: Snp Genotyping Imputation and Filtering For Regulatory Snpsmentioning
confidence: 99%
See 3 more Smart Citations